Sobrevivência de Xanthomonas axonopodis pv. manihotis em manipueira sob condições ambientais - De Faria Theodoro, Gustavo [UNESP]; Maringoni, Antonio Carlos [UNESP] (My University, 2002)
The objective of this work was to evaluate the survival of a Xanthomonas axonopodis pv. manihotis (Xam) strain, resistant to streptomycin sulfate, in manipueira (cassava residue) incubated under environmental conditions, in three periods of the year (March, July and October 2000). A semi-selective culture medium and the polymerase chain reaction (PCR) or biological amplification (BIO-PCR) methods were used. The pH and the total acidity of the manipueira were determined during the incubation period. The strain survived less than 24 hours in the three periods of the year. The PCR or BIO-PCR method was not effective in monitoring the strain survival in manipueira, as it showed contradictory and unreliable results. An increase in total acidity and a decrease in pH of the manipueira were observed, explaining the survival behavior of Xam strain.
Survival of Xanthomonas axonopodis pv. manihotis in manipueira under environmental conditions
Keywords: Acidity; Bacteria; Incubation; pH; Residues